Rehabilitation Following Posterior Shoulder Stabilization - Brandon T Goldenberg (North American Sports Medicine Institute, 2021)
Posterior shoulder instability has been noted in recent reports to occur at a higher prevalence than originally believed, with many cases occurring in active populations. In most cases, primary surgical treatment for posterior shoulder instability—a posterior labral repair—is indicated for those patients who have failed conservative management and demonstrate persistent functional limitations. In order to optimize surgical success and return to a prior level of function, a comprehensive and focused rehabilitation program is crucial. Currently, there is a limited amount of literature focusing on rehabilitation after surgery for posterior instability. Therefore, the purpose of this clinical commentary is to present a post-surgical rehabilitation program for patients following posterior shoulder labral repair, with recommendations based upon best medical evidence.